2012
DOI: 10.1016/j.bone.2012.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of proton irradiation followed by hindlimb unloading on bone in mature mice: A model of long-duration spaceflight

Abstract: Bone loss associated with microgravity unloading is well documented; however, the effects of spaceflight-relevant types and doses of radiation on the skeletal system are not well defined. In addition, the combined effect of unloading and radiation has not received much attention. In the present study, we investigated the effect of proton irradiation followed by mechanical unloading via hindlimb suspension (HLS) in mice. Sixteen-week-old female C57BL/6 mice were either exposed to 1 Gy of protons or a sham irrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 32 publications
6
32
0
Order By: Relevance
“…Our findings are consistent with previous reports that characterized the functional adaptation to mechanical loading in both the diaphyseal cortical [44,[54][55][56] and cancellous [45,46] compartments in rodents. Radiation exposure did not affect the structure of the cortical compartment in this study, consistent with results of others using gamma, iron, and proton radiation [52,53], and with our previous findings using gamma radiation [28,31].…”
Section: Discussionsupporting
confidence: 95%
See 1 more Smart Citation
“…Our findings are consistent with previous reports that characterized the functional adaptation to mechanical loading in both the diaphyseal cortical [44,[54][55][56] and cancellous [45,46] compartments in rodents. Radiation exposure did not affect the structure of the cortical compartment in this study, consistent with results of others using gamma, iron, and proton radiation [52,53], and with our previous findings using gamma radiation [28,31].…”
Section: Discussionsupporting
confidence: 95%
“…Although previous results demonstrated radiation (1-2 Gy) reduces cancellous but not cortical bone geometry [52,53], axial loading exerts an anabolic effect on both cancellous and cortical tissue [44,[54][55][56]. Therefore, we also analyzed cortical bone adaptation and found that Axially Loaded Contralateral Control Sham Irradiated Fig.…”
Section: Geometrymentioning
confidence: 82%
“…Loss of bone due to chronic inactivity or decreased mechanical demand (e.g. due to plaster cast immobilisation, bed rest or hindlimb suspension) has been demonstrated in multiple vertebrate species, including humans, monkeys, mice, rats, turkeys, dogs and sheep (Gross and Rubin, 1995;Li et al, 2005a;Lloyd et al, 2012;Rubin et al, 1988;Turner et al, 2006;Young et al, 1983) (Table 1). Cast immobilisation for as little as 10 days has been shown to result in osteopenia in rodents, as evidenced by decreased dry bone mass, bone mineral density and metaphyseal bone volume (Delling et al, 1970;Hott et al, 2003;Rantakokko et al, 1999;Weinreb et al, 1989).…”
Section: Disuse-induced Bone Lossmentioning
confidence: 99%
“…c 2 g/V. Prior to our work, the longest time period reported for hindlimb unloading experimentation was no more than 30 days for both rats (Xu et al, 2014) and mice (Lloyd et al, 2012). We extended the hindlimb unloading period to a time comparable to the length of the MDS mission (3 months) and, at the same time, we investigated alterations of the bone structure and function in a larger number of animals, thus improving the statistical analyses using both micro-CT techniques (CB-μCT and SR-μCT).…”
Section: Discussionmentioning
confidence: 98%
“…b HLU/V. of femoral length (Lloyd et al, 2012), total volume (TV), bone volume (BV), bone volume density (BV/TV), endocortical surface (Lloyd et al, 2012), angle between the femoral shaft and the femoral neck are shown in Table 1. The parameters describing the bone structural microarchitecture showed significant differences in HLU vs. the other two groups (Vivarium and 2 g) except for the length and the neck/ diaphysis angle.…”
Section: 1mentioning
confidence: 99%